A study of the production of English relative clauses by L1 Malay speakers in Malaysia / Nohra Dinkha Rabin - Nohra Dinkha , Rabin (2019)
This study focusses on Syntax. It aims to measure the syntactic knowledge of thirty (30) Malaysian first language (L1) adult Malay speakers in producing English Relative Clauses (henceforth, ERCs) through sentence combination task. The framework used to detect this was based on the Noun Phrase Accessibility Hierarchy (henceforth, NPAH) proposed by Keenan and Comrie (1977). Based on the categorization of the NPAH, there are six types of ERCs, these are: subject (SU), direct (DO), indirect object (IO), object of preposition (OPREP), genitive (GEN), and object of comparison (OCOMP). From the difficulty order (SU> DO> IO> OPREP> GEN> OCOMP) which was hypothesized by the NPAH, it is predicted that the SU type is the easiest and the OCOMP is the hardest. Based on the aim of the current study, two research questions were formulated. Firstly, which type of English relative clause, based on the NPAH, is the easiest and hardest for the Malaysian L1 Malay participants to produce, and secondly, what types of deviations, if they exist, are made by the Malaysian L1 Malay participants when producing English relative clauses. This study is quantitativequalitative in nature. The quantitative aspect is the statistical analysis derived from the data results while the qualitative aspect refers to the data generated from 540 combined sentences through the sentence combination task which was the approach used to extract the data. Findings indicated that the easiest ERC type based on NPAH for the participants was the SU (percentage of correct sentences on SU=63%) and the hardest one was the OPREP (percentage of correct sentences on OPREP=27%). The reason for this could be attributed to the participants’ L1 interference. This study also noted that of the four deviations types detected in the ERC sentences comprising incorrect relative pronouns selection (IRPS), non-adjacency (NA), omission of preposition (OP), and passivization (Pssv.), the most common was IRPS. The reason behind this could also be attributed to the participants’ L1 interference. The participants seemed to experience great difficulty in producing correct sentences on ERCs. The result showed that they are not fully aware of the formation of ERCs in which they made 241 correct sentences out of 540 total sentences on all the six ERC types. It is, thus, revealed that the participants are only (44.6%) syntactically knowledgeable of producing the structure of ERCs through the sentence combination task. On the other hand, they produced 299 incorrect sentences out of 540 total sentences for all the ERC types (percentage of incorrect sentences on all ERC types=55.4%). The main reason behind this may be, once more, attributed to the effect of their native language (Malay) which greatly interfered in their answers. This study is confined to looking at the productions of ERCs by Malaysian L1 Malay speakers only, thus, findings cannot be generalized to other Malaysian L1 speakers of Chinese or Tamil.